Electronic Noses and Olfaction 2000 : Proceedings of the 7th International Symposium on Olfaction and Electronic Noses, Brighton, UK, July 2000 /: Proceedings of the 7th International Symposium on Olfaction and Electronic Noses, Brighton, UK, July 2000. (2001) - Gardner, Julian W; Persaud, Krishna C
No abstract available